ANALISIS TINGKAT PENGEMBALIAN INVESTASI (RETURN ON INVESTMENT) DAN RISIKO PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) PADA BANK NEGARA INDONESIA (BNI) KANTOR CABANG GUNUNGSITOLI - Bate'e, Pius Berkat Iman; Hulu, Perlindungan Faebuadodo; Telaumbanua, Aferiaman; Bate'e, Maria Magdalena (Jurnal Suluh Pendidikan, 2025)
This study aims to analyze the level of return on investment, ROI) and the risk of financing the People's Business Credit (KUR) at the Indonesian State Bank of the Gunungsitoli Branch Office. By using quantitative data obtained from financial statements and credit statistics, this study explores the relationship between ROI and Non-Performing Loan (NPL) which reflects the risk in providing credit. The analysis methods used include regression analysis and financial ratios to measure investment performance and credit risk. The results showed that there was a significant relationship between ROI and the NPL level, where the increase in NPL had a negative impact on ROI. These findings provide important insights for bank management in decision making related to KUR financing strategies, as well as their application for the development of micro and small businesses in the area. Thus, this research is expected to be a reference to increase the effectiveness of risk management in KUR financing in the future.